Optimization of sorption of Pb (II) from water using rice bran - Hasan S.H.; Ranjan D.; Bhattacharjee B.N.; Talat M. (My University, 2025)
Response Surface Methodology (RSM), which is a statistical technique, was used for the optimization of the sorption of Pb (II) from aqueous solution using agricultural waste rice bran. For this purpose a 24 full factorial Central Composite Design (CCD), which is one of the important design of RSM, was utilized to investigate various parameters such as pH, initial [Pb(II)], temperature and biomass dose which are effecting the sorption process. The maximum sorption of Pb (II) was found to be 112.0 mg/ g at 20 °C, pH 5.5, [Pb (II)] 200 mg/L and a biomass dose of 300 mg/50 mL aqueous solution. Multiple regression analysis, 3D response and contour plots and optimization curves were used to further evaluate, confirm and optimize the experimental results. Finally a model was developed for predicting the uptake of Pb (II). The predicted values were found to be in good agreement with the experimental results. Thus the proposed model can be employed for the better removal of Pb (II) with minimum experimental set up. © 2008 Springer-Verlag.